Pengembangan Game Edukasi Matematika Untuk Meningkatkan Kemampuan Berpikir Komputasional Siswa Kelas VII - Yudi Hartawan, I Gusti Nyoman; Swarmantara, I Putu Adhitya; Suweken, Gede (Universitas Pekalongan, 2025)
This study aims to develop a mathematics educational game to enhance the computational thinking skills of seventh-grade students in relation to data and diagram materials. The development of the educational game utilizes the ADDIE model, which was developed with the assistance of Construct 3 software. The validity of the material and media was evaluated by experts using the LORI questionnaire. Practicality was assessed through the User Experience Questionnaire (UEQ). Effectiveness was measured by calculating the average N-Gain score. The results of the material validity test showed a validity percentage of 95% with a feasible criterion. The media expert assessment obtained a validity percentage of 95% with a feasible criterion. The results of a limited trial on 44 students and one teacher showed that the responses of teachers and students on the aspects of attractiveness, accuracy, stimulation, and novelty were included in the superior criteria, while the aspects of clarity and efficiency were included in the good criteria. Then, the results of the educational game obtained an average N-Gain score of 0.71, which falls within a high category. Thus, the developed mathematics educational game is declared valid, feasible, practical, and effective. This mathematics educational game can improve students' computational thinking skills and create a fun learning environment.